Avaliação do papel do sistema purinérgico e dopaminérgico no efeito antidepressivo promovido por MK-801 em peixe-zebra (Danio rerio) - Souza, Raquel Bohrer da Silva (2015)
Depression is a serious and recurrent disease characterized by anhedonia, loss of interest in daily activities, appetite, and sleep disturbances, reduced concentration and psychomotor agitation. Antidepressant drugs currently used have a very slow onset of action, with that comes the need for fast-acting treatments. Therefore, there is a growing interest in NMDA antagonists as a target for the development of new antidepressant drugs. Considering that the purinergic and dopaminergic systems are involved in anxiety, depression, and sleep, we characterize the role of these signaling pathways on antidepressant effects induced by MK-801 in zebrafish. The animals treated with MK-801 at 5, 10, 15, and 20 μM during 15, 30, and 60 minutes showed higher permanence in the top area of the tank, in comparison with the control group, indicating an antidepressant effect induced by this drug. The animals treated with MK-801 remained within 2 hours in the top of the tank when treated with 5 μM MK-801 and 4 hours when treated with 20 μM MK-801, returning to basal levels 24 hours after exposure.The repeated treatment did not induce cumulative effects, since animals treated daily for seven days showed the same pattern of behavioral response observed from the first day until the 7th day. In order to investigate the action of agonists and antagonists of A1 and A2A receptors and the influence of modulation on adenosine levels in antidepressant effects induced by MK-801, animals were pretreated with Caffeine, DPCPX, CPA, ZM 241385, CGS 21680, AMPCP, EHNA, dipyridamole, and NBTI before the exposure to MK-801 for 30 minutes. The nonselective adenosine receptor antagonist Caffeine (50 mg/kg) and the selective A1 adenosine receptor antagonist DPCPX (15 mg/kg) blocked the behavioral changes induced by MK-801. Dipyridamole (10 mg/kg), a selective inhibitor of nucleoside transport (NT), exacerbates the behavioral changes induced by MK-801. Dopamine receptor antagonists (sulpiride and SCH23390) did not induce changes on the behavioral alterations induced by MK-801. Our results have shown that the antidepressant effects induced by MK-801 in zebrafish are mediated by the activation by A1 adenosine receptor.